Perancangan Prototype Aplikasi Deteksi dan Pelacakan Manusia pada Video - Valentin Gea Affila Pradika; I Gusti Agung Gede Arya Kadyanan (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
The detection and tracking of humans in videos have gained significant attention due to their applications in various fields such as surveillance, activity recognition, and human-computer interaction. This article presents the design and development of a prototype application for human detection and tracking in videos. The use of the prototype methodology allows for early feedback, demonstrates the functionality and features, facilitates effective collaboration, and helps save time and costs in the development process. By following this methodology, the prototype application for human detection and tracking in videos is expected to provide accurate and reliable results, meeting the needs of users in various domains.